The Usage of a Variety of Languages in WhatsApp Group among Youth - Putri Ramadhaningrum; Sri Muryati; Muhlis Fajar Wicaksana (2022)
This research aims at describing the form of slang based on changes in the sound structure of the language and the form of vocabulary as well as the types of meaning and function of vocabulary used in the WhatsApp group of teenagers in Sanggrahan village, Sukoharjo regency. The method used in this research is descriptive qualitative. Data was collected by means of screenshots of conversations in the Sanggrahan Youth Whatsapp group, and recorded the slang vocabulary that the respondents used. Methods of data analysis using distribution techniques. This research found the usage of 56 slang vocabulary words. The findings are (1) there are two changes in the form of slang (phonological and morphological structure); (2) the denotative meaning is more dominant, and (3) the functional variations in the use of slang vocabulary (knowing the speaker's feelings, the attitude of the interlocutor, the context of speech, and just contact with other people).